AN EFFICIENT AND REPRODUCIBLE METHOD FOR IN VITRO PROPAGATION OF CASSIA ALATA L. – AN IMPORTANT WOODY MEDICINAL PLANT - MD RAFIQUE AHMED; MOHAMMAD ANIS; IM AREF (International Journal of Pharma and Bio Sciences, 2013)
A rapid and efficient protocol for the large-scale propagation of an important woody medicinal plant, Cassia alata L., is described. Cotyledonary node (CN) obtained from 15 day-old aseptic seedling were used as an explant and their morphogenetic potential was tested on MS media with various concentrations (0.5–12.5 µM) of 6-benzyladenine (BA), Kinetin (Kn), and 2-isopentinyl adenine (2iP) alone or in combination with different concentrations (0.1 - 1.0 µM) of naphthalene acetic acid (NAA), indole-3-butyric acid (IBA), indole-3-acetic acid (IAA). Among the single treatment, BA at an optimal concentration of 7.5 µM was most effective in inducing multiple shoots where 90% explants responded with an average shoot number (9.6 ± 0.3) and shoot length (1.7 ± 0.1 cm) after 6 weeks of culture. A better shoot differentiation and elongation was achieved in a combined treatment of BA (7.5 µM) and IBA (0.5 µM). Repeated subculturing of the explant in the fresh MS medium promoted a higher rate of shoot multiplication where 25.2 ± 0.9 well-grown healthy shoots with an average shoot length of 4.0 ± 0.0 cm were obtained by end of fourth subculture passage. Rooting was best induced in shoots excised from proliferated shoot cultures on MS medium augmented with an optimal concentration of 0.5 µM IBA. The in vitro-raised plantlets with well-developed shoots and roots were successfully established in thermocol cups containing soilrite and eventually transferred in garden soil with 84% survival rate. The results of this study provide the first report on in vitro plant regeneration of Cassia alata.